2017
DOI: 10.1371/journal.pone.0188135
|View full text |Cite
|
Sign up to set email alerts
|

The antiviral drug tenofovir, an inhibitor of Pannexin-1-mediated ATP release, prevents liver and skin fibrosis by downregulating adenosine levels in the liver and skin

Abstract: BackgroundFibrosing diseases are a leading cause of morbidity and mortality worldwide and, therefore, there is a need for safe and effective antifibrotic therapies. Adenosine, generated extracellularly by the dephosphorylation of adenine nucleotides, ligates specific receptors which play a critical role in development of hepatic and dermal fibrosis. Results of recent clinical trials indicate that tenofovir, a widely used antiviral agent, reverses hepatic fibrosis/cirrhosis in patients with chronic hepatitis B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 60 publications
2
34
0
Order By: Relevance
“…Recently, inhibition of Cx43‐based gap junctions and hemichannels was found to lower the degree of thioacetamide‐triggered liver fibrosis accompanied by superoxide dismutase overactivation and reduced production of inflammatory proteins in mice (Table ) . Using the same mouse model, tenovir, a widely applied antiviral agent, was found to inhibit Panx1‐mediated release of adenosine triphosphate and to counteract liver fibrosis . This complies with a study showing reduced collagen content, hepatic stellate cell activation, inflammation, and regeneration in Panx1 ‐/‐ mice upon repeated treatment with carbon tetrachloride …”
Section: Pathophysiology Of Connexin and Pannexin (Hemi)channelssupporting
confidence: 77%
“…Recently, inhibition of Cx43‐based gap junctions and hemichannels was found to lower the degree of thioacetamide‐triggered liver fibrosis accompanied by superoxide dismutase overactivation and reduced production of inflammatory proteins in mice (Table ) . Using the same mouse model, tenovir, a widely applied antiviral agent, was found to inhibit Panx1‐mediated release of adenosine triphosphate and to counteract liver fibrosis . This complies with a study showing reduced collagen content, hepatic stellate cell activation, inflammation, and regeneration in Panx1 ‐/‐ mice upon repeated treatment with carbon tetrachloride …”
Section: Pathophysiology Of Connexin and Pannexin (Hemi)channelssupporting
confidence: 77%
“…A ). Because we had previously shown that tenofovir treatment diminishes extracellular adenosine levels by inhibiting ATP export via pannexin‐1, we next determined whether increasing extracellular adenosine levels by treatment with dipyridamole reversed the effect of tenofovir on osteoclast formation and found that dipyridamole completely reversed the effect of tenofovir on osteoclast differentiation (IC 50 = 0.3μM; Fig. A ).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have found that direct activation of A2AR inhibits NFκB translocation to the nucleus and inhibits osteoclast differentiation by a mechanism that involves cAMP‐PKA‐ERK1/2 signaling, signals downstream of Gnas . Dipyridamole, which does not affect bone homeostasis in A2AR knockout mice, most likely reverses the effect of tenofovir by restoring extracellular adenosine levels that are reduced by tenofovir treatment …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations